Skolt Sami language elements in the linguistic landscape in Norway and Finland: presence or absence? A study on Sami language policy and indigenous language reality in four settlements in the Skolt Sami homeland - Austad-Sivertsen, Nina Merete (UiT Norges arktiske universitet, 2022)
The Skolt Sami people have their traditional homeland in Eastern Finnmark (Norway), Northern Lapland (Finland), and on the Kola Peninsula in Northwest Russia. Skolt Sami language is classified as a nearly extinct indigenous language according to the UNESCO Atlas of the World’s Languages in Danger (Moseley and Nicolas, 2017), with just over 300 speakers (Jakhelln, 2021, p. 8). This thesis is intended as a contribution to the present discourse on the visibility of indigenous languages in public space, and the influence of language policy on the conditions for indigenous languages. It further aims at illustrating the relevance of visibility in public space to power relations and representation in civil society through case studies of four settlements in the Skolt Sami homeland, governed under two different national Sami language policies. The thesis documents the linguistic landscape of Njauddâm and Ǩeârkknjargg (Norway), Če’vetjäu’rr and Aanar (Finland). A comparison is made between the Sami language policies and the indigenous language realities in the areas in question, by looking at the occurrence of signage in Skolt Sami language in the public space in these areas. Here, I examine what connections, if any, can be identified between Sami language policy and the occurrence of signage in Skolt Sami language in public space in the researched areas of the Skolt Sami homeland? To answer this question, I will ask: what characterises the Sami language policies in Norway and Finland? And: to what extent is Skolt Sami language represented on signage in the public space in the researched areas of the Skolt Sami homeland? By looking at the Skolt Sami case, I find there is compelling evidence to claim that there is a connection between national Sami language policy and indigenous language reality in the case of the visibility of Skolt Sami signs in the public space in the Skolt Sami homeland. Keywords: Linguistic landscape, Skolt Sami language, indigenous language, Sami language policy, language visibility, public space